Exploring the Impact of Youth Leadership Development Programs in TVET: Systematic Literature Review - Norzeha Othman; Nur Ashikin Mohd Sharif (Journal of TVET and Technology Review, 2024)
Technical and Vocational Education and Training (TVET) systems play a crucial role in preparing young individuals with practical skills and essential competencies needed for entering the workforce. Within this framework, the incorporation of youth leadership development programs presents a promising avenue to not only hone technical proficiencies but also cultivate leadership qualities vital for personal growth, civic engagement, and societal transformation. Moreover, establishing influential leadership within higher education involves seizing available opportunities and making informed decisions to effectively guide institutions forward. Through systematic analysis various of scholarly resources, this review to uncover the impact of youth leadership in development on personal, civic engagement dan social change. Following the PRISMA framework encompassing Population, Intervention, Comparison, Outcomes, and Specific exclusions, this systematic review was meticulously structured. Data were sourced from platforms such as Scholar, Science Direct, ResearchGate, OECD Library, Scopus, Springer, and Research Leap. The comprehensive review process involved scrutinizing all identified papers and conducting quality assessments. Ultimately, twenty articles meeting the criteria were meticulously selected for data extraction, organization, and analysis through narrative synthesis. The review identified the impact on youth through programmed of youth leadership in their development of personal, civic and social change. Empowering young individuals by fostering their skills and creating favorable conditions, experiences, and opportunities allows them to engage actively and meaningfully within their community.